A criação do Centro de Atenção Psicossocial Espaço Vivo - Ribeiro, Sérgio Luiz [UNESP] (Conselho Federal de Psicologia, 2004)
This article deals with the process of the Brazilian psychiatric reform, since the 80’s, that led to the implementation of the alternative services in mental health. It discusses more specifically the creation and organization of the Psychosocial Attention Center “Living Space” of Botucatu-SP, Brazil. This was possible due to the transformations in the care of psychotic patients of “Professor Cantídio de Moura Campos” Hospital. It considers the importance of team work and the respect to the singularity and subjectiveness of the ones involved in the process of changing the attendance of mental suffering.

Este artigo trata do processo da reforma psiquiátrica brasileira, a partir dos anos 80, que levou ao surgimento de serviços alternativos em saúde mental. Mais especificamente, aborda a criação e organização do Centro de Atenção Psicossocial Espaço Vivo, de Botucatu-SP, que ocorreu a partir das transformações no atendimento aos pacientes psicóticos do Hospital Professor Cantídio de Moura Campos. Faz reflexões sobre a importância do trabalho em equipe e do respeito à singularidade e subjetividade dos envolvidos nesse processo de mudança da forma de atendimento ao sofrimento mental.
The creation of the psychosocial attention center “living space”
Keywords: Psychosocial attention center; Mental health; Alternative services; Interdisciplinary team; Brazilian psychiatric reform; Centro de Atenção Psicossocial; Saúde mental; Serviços Alternativos; Equipe interdisciplinar; Reforma psiquiátrica brasileira